Internalization of port congestion: strategic effect behind shipping line delays and implications for terminal charges and investment. Issue 1 (2nd January 2017) - Jiang, Changmin; Wan, Yulai; Zhang, Anming
ABSTRACT: This paper develops a theoretical model to analyze the congestion internalization of the shipping lines, taking into account the 'knock on' effect (i.e. the congestion delay passed on from one port-of-call to the next port-of-call). We find that with the presence of the knock-on effect, liners will operate less in terminals, and an increase of a liner's operation in one terminal will decrease its operation in the other. If the liners are involved in a Stackelberg competition, whether they operate more or less in a terminal under the knock-on effect depends on the comparison between the marginal congestion costs of terminals. Furthermore, we find that the coordinated profit-maximizing terminal charges are higher than both the socially optimal terminal charges and the independent profit-maximizing terminal charges. When the knock-on effect is small, the independent profit-maximizing terminal charges are set at higher levels than the socially optimal terminal charges; but when the knock-on effect is sufficiently large, this relationship may reverse. Besides, the capacity investment rules are the same for welfare-maximizing terminal operator and coordinated profit-maximizing terminal operator, while independent profit-maximizing terminal operators invest less in capacity. The larger the knock-on effect, the larger this discrepancy.